Marine litter present situation in Costa Rica - Abarca-Guerrero, Lilliana (2023)
In 2007, the United Nations indicated the concern around the impact of solid waste affecting the oceans as a result of land-based and marine activities, threatening the health of the oceans, food security, food quality, human health and tourism and livelihoods for those that depend on the ocean. Costa Rica has two coasts, one in the Pacific Ocean and the other in the Caribbean Sea, with abundant natural resources in both marine and terrestrial ecosystems. However, they are severely threatened due to the resources abuse and the anthropogenic activities. Due to the above and in addition to the global interest in protecting the oceans, the government of Costa Rica embarked in the formulation of the National Marine Litter Plan, with the participation of actors from all sectors. For this, a baseline analysis was carried out with information collected from international and national literature, with participatory workshops as a means for data collection, on site visits to fishermen’s associations in the Pacific and the Caribbean, interviews, questionnaires and discussions about the relevant issues. The results of these enquires are presented in this article. It summarizes the contribution of land and marine-based sources, the impact on ecosystems, the monitoring activities that are carried out, the different education, awareness and information programs available, the international and national regulations, ending with an analysis of the research and development activities and the challenges for innovation. Conclusions are also presented on the current state of marine litter for the topics analyzed.